An ERP Investigation of Orthographic Priming with Relative-Position and Absolute-Position Primes - Grainger, Jonathan (2009)
The present study used event-related potentials to examine the time-course of relative-position and absolute-position orthographic priming. Relative-position priming was examined using primes formed by a concatenated subset of the target word’s letters (e.g., cllet/COLLECT vs. dlema/COLLECT), and absolute-position priming was investigated using hyphenated versions of these primes (c-lle-t/COLLECT vs. d-lem-a/COLLECT). Both manipulations modulated the ERP waveform starting at around 100 ms post-target onset and extending into the N400 component. The first clear manifestation of priming was found in the N250 component, where hyphenated primes were found to have an earlier, more robust and more widely distributed effect than the concatenated primes. On the other hand, both prime types had similar effects on N400 amplitude. These results provide important information about the time-course of activation of location-specific and location-invariant (word-centered) orthographic representations during visual word recognition.